Comparison of Perception and Academic Outcome of Final Year BDS Students Regarding Lecture-Based Learning and Problem-Based Learning : Comparison between Lecture vs. Problem-Based Learning - Khalil, Aamna; Afreen, Ammarah; Amjad, Sadaf; Afreen, Zara; Siddiqui, Muhammad Omer; Iqbal, Qudsia (Pakistan Journal of Health Sciences, 2025)
This study explores the differences in student perception and academic outcomes between traditional lecture-based learning and problem-based learning methods in an educational setting. Objective: To find the effectiveness of Problem-Based Learning (PBL) versus Lecture-Based Learning (LBL) in enhancing academic performance and student satisfaction. Methods: Comparative cross-sectional study was carried out among final year BDS students at Watim Medical and Dental College Rawalpindi. The study evaluated lecture-based learning (LBL) versus problem-based learning (PBL) in Prosthodontics and Operative dentistry. LBL consisted of interactive lectures with clear objectives, while PBL involved group-based problem solving over two months. Academic outcomes were assessed via class tests, with feedback gathered through a structured questionnaire. Data were analyzed using SPSS version 21.0. Results: A total of 131 final year BDS students were included. Both genders were considered however majority were females (74%). Mostly participants appreciated both teaching methodologies (58%), a significant proportion favored lecture-based learning (26%) over problem-based learning (11.5%). Perceptions varied on the effectiveness of each method in fostering understanding, self-learning habits, and analytical skills. Many participants expressed dissatisfaction with resource availability and syllabus coverage in PBL sessions, despite positive views on facilitator training. Exam results showed a higher pass rate with PBL (76.3%) compared to LBL (56.5%), but satisfaction with PBL did not significantly influence exam outcomes (p>0.05). Conclusions: The study concluded that future research should focus on optimizing educational methodologies in dental education to effectively prepare students for the complex demands of healthcare through innovative and balanced approaches.